Duck egg-drop syndrome caused by BYD virus, a new Tembusu-related flavivirus. - Jingliang Su; Shuang Li; Xudong Hu; Xiuling Yu; Yongyue Wang; Peipei Liu; Xishan Lu; Guozhong Zhang; Xueying Hu; Di Liu; Xiaoxia Li; Wenliang Su; et al. (PLoS ONE, 2011)
Since April 2010, a severe outbreak of duck viral infection, with egg drop, feed uptake decline and ovary-oviduct disease, has spread around the major duck-producing regions in China. A new virus, named BYD virus, was isolated in different areas, and a similar disease was reproduced in healthy egg-producing ducks, infecting with the isolated virus. The virus was re-isolated from the affected ducks and replicated well in primary duck embryo fibroblasts and Vero cells, causing the cytopathic effect. The virus was identified as an enveloped positive-stranded RNA virus with a size of approximately 55 nm in diameter. Genomic sequencing of the isolated virus revealed that it is closely related to Tembusu virus (a mosquito-borne Ntaya group flavivirus), with 87-91% nucleotide identity of the partial E (envelope) proteins to that of Tembusu virus and 72% of the entire genome coding sequence with Bagaza virus, the most closely related flavivirus with an entirely sequenced genome. Collectively our systematic studies fulfill Koch's postulates, and therefore, the causative agent of the duck egg drop syndrome occurring in China is a new flavivirus. Flavivirus is an emerging and re-emerging zoonotic pathogen and BYD virus that causes severe egg-drop, could be disastrous for the duck industry. More importantly its public health concerns should also be evaluated, and its epidemiology should be closely watched due to the zoonotic nature of flaviviruses.